Patterns of spatial and temporal dynamics of mixed Mytilus edulis and M. trossulus populations in a small subarctic inlet (Tyuva Inlet, Barents Sea) - Marchenko, Julia; Khaitov, Vadim; Katolikova, Marina; Sabirov, Marat; Malavenda, Sergey; Gantsevich, Michael; Basova, Larisa; Genelt-Yanovsky, Evgeny; Strelkov, Petr (Frontiers in Marine Science, 2023)
Subarctic populations of “cryptic” blue mussel species Mytilus edulis (ME) and M. trossulus (MT) are less studied than Arctic and boreal populations. Ecological features of ME and MT in sympatry are poorly known everywhere. We studied the habitat segregation of ME and MT and the interannual dynamics of their mixed settlements at the Murman coast of the Barents Sea, the northeastern boundary of the Atlantic littoral mussel communities. Previous data on mussels from this area are 50-100 years old. The 3-km-long Tyuva Inlet (Kola Bay) was used as the study site. Mussels were found in the littoral and the sublittoral down to a depth of 4 m. Their characteristic habitats were sandbanks, littoral rocks, sublittoral kelp forests and “the habitat of the mussel bed” in the freshened top of the inlet. The main spatial gradients explaining the variability of demographics of the settlements (abundance, age structure, size) were associated with the depth and the distance from the inlet top. ME and MT were partially segregated by depth: ME dominated in the sublittoral and MT, in the littoral. In addition, ME dominated throughout the mussel bed. The ratio of species in the mixed settlements varied over time: between 2004 and 2010 the proportions of MT decreased everywhere, by 22% on average. The habitat distribution of mussels apparently changed with time: we found that mussels were abundant in kelp forests, where they had rarely been observed in the 20th century. We suggest that the spatial and temporal dynamics of subarctic mussels can be partly explained by the competition between ME and MT and their differing sensitivity to environmental factors.